P16INK4a-siRNA nanoparticles attenuate cartilage degeneration in osteoarthritis by inhibiting inflammation in fibroblast-like synoviocytes. (17th May 2022) - Park, Hyewon; Lee, Ha-Reum; Shin, Hyo Jung; Park, Ji Ah; Joo, Yongbum; Kim, Sun Moon; Beom, Jaewon; Kang, Seong Wook; Kim, Dong Woon; Kim, Jinhyun
Abstract : PLGA nanoparticle encapsulating p16INK4a siRNA can attenuate osteoarthritis by targeting fibroblast-like synoviocyte. Abstract : In osteoarthritis (OA), chondrocytes in cartilage undergo phenotypic changes and senescence, restricting cartilage regeneration and favoring disease progression. Although senescence biomarker p16INK4a expression is known to induce aging by halting the cell cycle, therapeutic applications for p16INK4a targeting are limited. Here, we aimed to reduce cartilage damage and alleviate pain using p16INK4a nanoparticles in OA. The p16INK4a expression of human OA chondrocytes and synoviocytes from patients with knee OA was measured and the levels of p16INK4a, tumor necrosis factor (TNF)-α, interleukin (IL)-1β, IL-6, and matrix metalloproteinase (MMP) 13 were examined. p16INK4a siRNA was encapsulated into poly (lactic- co -glycolic acid) (PLGA) nanoparticles and characterized. The partial medial meniscectomy (pMMx) model was performed for the OA model which was investigated by molecular analysis and behavioral tests. The expression of p16INK4a was increased in the synovium and articular cartilage from OA patients. p16INK4a siRNA-loaded PLGA nanoparticles (p16 si_NP) reduced the levels of TNF-α, IL-1β, and IL-6 especially in fibroblast-like synoviocytes (FLSs), and MMP13 in chondrocytes. Rhodamine-tagged NPs injected into the mouse knee joints were found mainly in the synovium. p16 si_NP injection in the pMMx model alleviated pain-associated behavior, and reduced cartilage damage and p16INK4a in the synovium, and MMP13, collagen X, and NITEGE in cartilage. The preferential reduction of p16INK4a in FLSs by the application of RNAi nanomedicine could contribute to the recovery of osteoarthritic cartilage and relieve pain, suggesting that p16INK4a may be a viable future therapeutic candidate.